Network economy in the context of digitalisation of society: approaches to definition and features of development - Mozalevskaya, Daniela A. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The essence of the network economy in the context of global digitalisation of society is analysed. The main approaches to understanding this phenomenon are presented. The advantages and disadvantages of network management of economic activity are revealed. Such specific properties of the network structure as self-reproducibility, interdependence of network elements, polycentricity, non-linearity, etc., are indicated. The implementation of network management, including in the current programmes of socio-economic development of the Republic of Belarus, is considered.
Keywords: network economy; network structure; digitalisation; forms of organisation of economic activity; clustering; human-centricity